GREEN SYNTHESIS OF THREE UNIQUE NANOPARTICLES FROM Hibiscus ficulneus L. AND ASSESSMENT OF THEIR POTENTIAL ANTIMICROBIAL PROPERTIES (Applied Biological Research, 2024)
The synthesis and characterization of various nanoparticles using the  extracts from Hibiscus ficulneus L., a medicinal plant known for its  therapeutic properties, were investigated. Nanoparticles of three metals,  namely silver, copper and zinc (used in the form of silver nitrate, copper  sulphate, and zinc sulphate) were synthesized. The presence of nanoparticles  was confirmed by observing a spectrum in visible range, which was carried  out using a UV-visible spectrophotometer. To observe the crystalline  structure, XRD analysis was performed. SEM analysis revealed uniformly  distributed silver nanoparticles on the surfaces of the cells. The silver  nanoparticles were spherical in shape with particle size in the range of 2 to 20  μm. The antimicrobial activity of the synthesized nanoparticles was evaluated  using the zone of inhibition method. The highest antimicrobial activity was  observed with silver nanoparticles as compared to the other silver nano particle extracts, particularly against Pseudomonas aeruginosa (20 mm).  These results highlight the significant antimicrobial potential of silver  nanoparticles against pathogenic bacteria. This study underscores the role of  terrestrial products as potential sources for pharmaceutical applications.
Keywords: Antimicrobial activity; Hibiscus ficulneus; nanoparticles; SEM; XRD